Identification of multiple replication stages and origins in the nucleopolyhedrovirus of anticarsia gemmatalis - Miele, Solange Ana Belen (2019)
To understand the mechanism of replication used by baculoviruses, it is essential to describe all the factors involved, including virus and host proteins and the sequences where DNA synthesis starts. A lot of work on this topic has been done, but there is still confusion in defining what sequence/s act in such functions, and the mechanism of replication is not very well understood. In this work, we performed an AgMNPV replication kinetics into the susceptible UFL-Ag-286 cells to estimate viral genome synthesis rates. We found that the viral DNA exponentially increases in two different phases that are temporally separated by an interval of 5 h, probably suggesting the occurrence of two different mechanisms of replication. Then, we prepared a plasmid library containing virus fragments (0.5–2 kbp), which were transfected and infected with AgMNPV in UFL-Ag-286 cells. We identified 12 virus fragments which acted as origins of replication (ORI). Those fragments are in close proximity to core genes. This association to the core genome would ensure vertical transmission of ORIs. We also predict the presence of common structures on those fragments that probably recruit the replication machinery, a structure also present in previously reported ORIs in baculoviruses.